DINAMIKA FORMULASI KEBIJAKAN PEMERINTAH PROVINSI DAERAH ISTIMEWA YOGYAKARTA DALAM PENATAAN PEDAGANG KAKI LIMA DI KAWASAN TERAS MALIOBORO - Sanastiti, Zahwa; Suranto (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2023)
The aim of this research is to determine the dynamics of the policy formulation for the relocation of Street Vendors (PKL) to the Malioboro Terrace by the DIY Provincial Government and the interests and behavior of the actors involved in the dynamics of the policy formulation for the relocation of Street Vendors (PKL) to the Malioboro Terrace. The results of this research show that the dynamics of policy formulation for the relocation of street vendors to Teras Malioboro by the DIY Regional Government went through various stages. The various stages, namely Problem Assessment, are carried out by reviewing Academic Papers and SWOT Analysis by the Regional Government and DIY DPRD. Determining the dynamic objective of policy formulation is to support the existing problem, namely the registration of the Yogyakarta Philosophy Axis with (UNESCO) as a world heritage. Furthermore, UPT Malioboro is one of the answers to formulating alternatives in the policy of relocating street vendors (PKL) in the Malioboro area to Teras Malioboro. In preparing the model, especially in institutions, the DIY Regional People's Representative Council (DPRD) is involved in preparing the Academic Paper. An alternative assessment of the dynamics of policy formulation by local governments under specific requirements to obtain a clearer picture of the feasibility or effectiveness of the program is to conduct a survey. The interests and behavior of the actors involved in the dynamics of policy formulation for the relocation of street vendors to Teras Malioboro use 4 strategies by behavior and actors in the dynamics of the policy for relocating street vendors (PKL) in the Malioboro area to Teras Malioboro